Effect of the coronavirus disease-2019 pandemic on the follow-up and treatment of patients with rosacea - Murat Durak; Özgür Gündüz (Galenos Publishing House, 2023)
Background and Design: This study aimed to investigate the effects of the precautions and preventive measures implemented during the coronavirus disease-2019 (COVID-19) pandemic on the follow-up and treatment processes of patients with rosacea who applied to the Skin and Venereal Diseases outpatient clinic of a university hospital in Türkiye. Materials and Methods: Age, sex, number of hospital admissions, prescribed topical and systemic treatments, total amount of treatment on a box basis, follow-up interval in multiple applications, and number of applications to the Ophthalmology Department were recorded before and during the COVID-19 pandemic. Results: No difference was found in the age and sex distributions of patients with rosacea who applied to the Skin and Venereal Diseases outpatient clinic during the COVID-19 pandemic compared with that before the pandemic. However, the total number of patients decreased. Furthermore, the total number of drugs prescribed to patients and the number of systemic drugs increased proportionally during the COVID-19 pandemic. In addition, the ratio of patients who continued their follow-up and the use of systemic drugs among these patients increased. Conclusion: In this study, the number of admissions decreased and the rate of patients who needed systemic treatment increased. Rosacea and similar dermatoses that required long-term follow-up could be evaluated via teledermatology during periods when application to outpatient clinics for follow-up becomes difficult such as during pandemics and natural disasters.